Metagenomic Evidence of Microbial Community Responsiveness to Phosphorus and Salinity Gradients in Seagrass Sediments - Fraser, Matthew W.; Gleeson, Deirdre B.; Grierson, Pauline F.; Laverock, Bonnie; Kendrick, Gary A. (Frontiers in Microbiology, 2018)
Sediment microorganisms can have profound influence on productivity and functioning of marine ecosystems through their critical roles in regulating biogeochemical processes. However, the identity of sediment microorganisms that mediate organic matter turnover and nutrient cycling in seagrass sediments is only poorly understood. Here, we used metagenomic sequencing to investigate shifts in the structure and functioning of the microbial community of seagrass sediments across a salinity and phosphorus (P) availability gradient in Shark Bay, Western Australia. This iconic ecosystem is oligotrophic and hypersaline with abundant seagrass meadows that directly contribute Shark Bay’s status as a World Heritage Site. We show that sediment phosphonate metabolism genes as well as enzyme activities increase in hypersaline conditions with lower soluble reactive phosphate in the water column. Given that sediment organic P content is also highest where P concentrations in the water column are low, we suggest that microbial processing of organic P can contribute to the P requirements of seagrasses at particularly oligotrophic sites. Seagrass meadows are often highly productivity in oligotrophic waters, and our findings suggest that an increase in the functional capacity of microbial communities in seagrass sediments to break down organic P may contribute to the high productivity of seagrass meadows under oligotrophic conditions. When compared to soil and sediment metagenomes from other aquatic and terrestrial ecosystems, we also show microbial communities in seagrass sediments have a disproportionately high abundance of putative phosphorus and sulfur metabolism genes, which may have played an important evolutionary role in allowing these angiosperms to recolonize the marine environment and prosper under oligotrophic conditions.